Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1,1/3+1/2:X= -4
1/2:X= -4-1/3
1/2:X= -13/3
X=1/2 : -13/3
X= -3/26
1. 1/3 + 1/2 : x = -4
=> 1/2 : x = -4 - 1/3
1/2 : x = -13/3
=> x = 1/2 : (-13/3)
x = -3/26
2. 3x - 30%.x = -5,4
3x - x = -18
2x = -18
=> x = -18 : 2
x = -9
a)\(12\left(2x-6\right)-43=5^3\)
\(12\left(2x-6\right)=125+43\)
\(12\left(2x-6\right)=168\)
\(\left(2x-6\right)=168:12\)
\(\left(2x-6\right)=14\)
\(2x=14+6\)
\(2x=20\)
\(x=20:2\)
\(x=10.\)
b) \(7\left(25-3x\right)=3^4-2^5\)
\(7\left(25-3x\right)=49:7\)
\(7\left(25-3x\right)=7\)
\(\left(25-3x\right)=7:7\)
\(\left(25-3x\right)=1\)
\(3x=25-1\)
\(3x=24\)
\(x=24:3\)
\(x=8.\)
23/4 nha
=> 16 . (x + 1) - 5 = 43
=> 16 . (x + 1) = 43 + 5
=> 16 . (x + 1) = 48
=> x + 1 = 48 : 16
=> x + 1 = 3
=> x = 3 - 1
=> x = 2
Vậy x = 2